Profile Of Traditional Jamu Business In Bengkulu City - agung trisusilo; Putri Suci Asriani; Apri Andani (Journal of Agri Socio Economics and Business, 2019)
This study attempts to make the profile of the "jamu traditional" business in Bengkulu City. This research used the survey method and had done from August till December 2017. This research used descriptive analysis, R/C ratio, and Return on Investment analysis. The owners stay in 7 sub-district in Bengkulu City. Sub-District Ratu Agung is the location in which most owners stay there. The are dominates women and in the age group 45-54 years old. They have the average experience 24, 23 years with educational level still just elementary school. At once the production process issued cost Rp. 75.750,15 while the income Rp. 189.000. R/C ratio 2,49 and return on investment 149,5%. So this business appropriate to do so. The owners have positive perception and hight motivation with their business.